Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters - Heo, Jun-Haeng; Hendrycks, Ed A.; Kim, Young-Hyo (Zootaxa, 2020)
Two new species of the genus Microlysias Stebbing, 1918 belonging to the family Tryphosidae Lowry & Stoddard, 1997 were collected from shallow Korean waters. The two new species are described as Microlysias rectangulatus and M. triangulus. The new species M. rectangulatus sp. nov. is similar to M. xenokeras, M. soela, and Orchomenella japonica. However, the new species can be distinguished from these species by having a subrectangular peduncular article 5 of antenna 2 and an elongated article 1 of the mandibular palp, nearly equal to palp article 3. M. triangulus sp. nov. is similar to M. xenokeras and M. soela. However, this species is characterized by the triangular shaped peduncular article 5 of antenna 2 and the slender propodus of gnathopod 1. These species are illustrated and compared to related species.